Tilt Observations at the Seafloor by Mobile Ocean Bottom Seismometers - Shiobara, Hajime; Ito, Aki; Sugioka, Hiroko; Shinohara, Masanao; Sato, Toshinori (Frontiers in Earth Science, 2021)
We had developed a broadband ocean bottom seismometer (BBOBS) and its new generation (BBOBS-NX) with the penetrator sensor system since 1999. With them, we have performed many practical observations to create a new research category of the ocean bottom broadband seismology. As the next step in seafloor geophysical observation, the BBOBS and the BBOBS-NX can be a breakthrough in realizing a geodetic observation network on the seafloor. Although vertical displacement observation by the absolute pressure gauge has been widely conducted in these years, other geodetic observations are rarely performed. A few trials to measure the seafloor tilt were performed, but those looked inadequate for practical observations. Note that the broadband sensor in our BBOBSs has the mass position signal output, which can be used to measure the tilt change. As the horizontal component noise level of the BBOBS-NX is good in the long period range, we expected it to be adequate for the tilt measurement. As the first evaluation, we performed a comparison with the water-tube tiltmeter. The result was comparable with resolution of better than 1 µ radian. A practical observation at the south off Boso Peninsula (KAP3 site) was conducted as the in-situ study from Apr. 2013. In Jan. 2014, a slow slip event (SSE) occurred near this site. The tilt data was processed by removing for steps, the mechanical relaxation, and tides. The results show a clear peak started from late December 2013. Two more 2-year-long tilt observations were started from 2015: one is at the KAP3 site and another is off Miyagi Prefecture at the slope to the Japan Trench. The later was recovered in 2017 with about 1.5-year-long data, which indicates large continuous tilt up to several tens of µ radian. This amount of tilt can be explained by a similar SSE already estimated. The mobile tilt measurement at the seafloor can be a powerful tool to study SSEs, as they are able to be located above the source area and also able to build an observation array for the practical study because of its low cost compared with a seafloor borehole site.